INVESTIGATING INDONESIAN SLANGY WORDS ON TIKTOK’S COMMENTS - Ida Zuraida Supri; Tajudin Nur (English Journal Literacy Utama, 2021)
This research aims to investigate the characteristics and functions of slang used by Indonesian netizens in the comments on TikTok. The method used in this research is a qualitative descriptive method proposed by Bogdan (1998:69). Data collections is conducted by reading the comments written by Indonesian netizens on TikTok, collecting data, classifying the types of slang, analyzing the functions of the slang found, and finally, drawing conclusions. The data source was taken from comments of netizens in TikTok. The theoretical framework used for the types of slang is based on the theory of Allan & Burridge (2006) and the theory of the functions of the slang is from Zhou and Fan (2013). The results of this study show that the morphological process of the slangy words found in the data analyzed are clipping (40%), blending (40%) and backformation (20%). The characteristics of the slangy words are creative (20%) and creative and fresh (80%). The function of the use of slangy words found in the data is to pursue self-identity (100%.)